Issues in University Administration in Nigeria - Ukozor, Conrad Ugochukwu; Ikechukwu, Blessing Ijeoma (Journal of Higher Education and Academic Advancement, 2024)
University administration is the engine room of the universities that determines the university’s development speed. University administration is the pillar that holds the universities and makes its function. This paper is a review research paper with the objective to examine issues hindering effective university administration in Nigeria. Relying on secondary data collected from print and online publications. Content analysis was adopted to scrutinize the data that gave the final data that were used in the paper. The paper concluded that poor funding, Integrated Personnel and Payroll Information System (IPPIS), corruption, lack of current data, inadequate staff, shortage of infrastructure facilities, brain-drain, political interferences and strike action are some of the problems hindering effective university administration in Nigeria. Based on these problems, the paper recommended that the government should increase the financial investment of university education. The government should remove universities from the Integrated Personnel and Payroll Information System (IPPIS) platform and employ more academic staff in all public universities in Nigeria. The government321 qewdsx3432qewzx should direct all anti-corruption agencies to monitor all the funds released to the university administration and artificial intelligence should be deployed for effective fit against corruption in the system. The government should ensure current university data are generated annually for effective university planning.